Dampak negatif Isu Tsunami Terhadap Sosial Ekonomi Masyarakat Purus V Kelurahan Purus di Kecamatan Padang Barat Kota Padang - Baini, Syaiful; Juita, Erna; Zuriyani, Elvi (Pendidikan Geografi, 2013)
ABSTRACT This study aimed to obtain information, analyze and discuss data about the negative impact of the Tsunami issues to the Socio Economic of the Society in Purus V Village in the district of Padang West.The type of this research was correlational descriptive. The study population is the Purus V Sub District West Padang city with a population of 386 households. The study sample in this research is proportional random sampling about 30% so that, the sample amounted to 117 households.Based on a simple linear regression analysis, double (multiple) and the correlation it can be concluded as follows: (1) the tsunami issue is impact negatively on people displacement / migration, since t> t table (3.246> 1.987), the power of the negative impact of the tsunami issue to the people displacement / migration is low (r = 0.290) and contributed very small. (8.4%) with the regression model Y = 16.72 + 0.294 X1, (2) the tsunami issue is impact negatively on the people income for t> t table (4.059> 1.670). the Strength of the negative impact of the tsunami issue to the low income levels is (r = 0.354) and contributed very small (12.5%) with the regression model Y = 19.522 + 2.82 X2, (3) the tsunami issue had no impact to the people livelihoods due to t <ttable (-0.141> 1.670 Strength of the negative impact of the tsunami issue to the peoples livelihood is very low (r = 0.013) and made no contribution to the regression model Y = 23.713-.041 X3 and (4) the tsunami issue impact negativelyto the people displacement / migration, income levels and livelihoods community together as Fhitung> F table (7.719> 3.150). the Strength of the negative impact of the tsunami issue to the three variables included medium (r = 0.412) and a contributed very small (17.0%) with the regression model Y = 14.510 + 0.222 X1 + 0.051 X2 + 2.12 X3. Key words : impact tsunami issues, socio economic, society